1995
DOI: 10.1159/000244193
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Neurotransmitters and Metabolites in the Cerebrospinal Fluid following Perinatal Asphyxia

Abstract: While the release of neurotransmitters is involved in the pathophysiology of brain damage following birth asphyxia, it also plays a role in endogenous defense against such damage. Levels of monoamines and the main cerebral monoamine metabolites in the cerebrospinal fluid (CSF) were measured in asphyxiated and control infants within 24 h after birth. The results indicate an increased turnover of noradrenaline (NA) and dopamine following asphyxia. Furthermore, the NA stores in the brain seem to be exhausted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Increasing FiO 2 levels facilitates posthypoxic cerebral cortical hyperoxia (47) and results not only in cerebral, but also in systemic, oxidative damage (48). Although the blood oxidative stress indicator levels in our study did not reveal any significant liberation of potentially highly damaging mediators, on the basis of previously published observations (12,49) (as there were no other significant differences between the two asphyxiated groups apart from the arterial PO 2 values) we presume the deleterious effects of hyperoxia on the neuronal cell membranes were caused either by increasing cerebral dopamine concentration (50,51) or by other lipid peroxidation products (52-55) not measured here. It also seems likely that the oxidative stress remained localized within the CNS, and the elevations in the biochemical markers become lost on dilution in the plasma (56).…”
Section: Discussionsupporting
confidence: 61%
“…Increasing FiO 2 levels facilitates posthypoxic cerebral cortical hyperoxia (47) and results not only in cerebral, but also in systemic, oxidative damage (48). Although the blood oxidative stress indicator levels in our study did not reveal any significant liberation of potentially highly damaging mediators, on the basis of previously published observations (12,49) (as there were no other significant differences between the two asphyxiated groups apart from the arterial PO 2 values) we presume the deleterious effects of hyperoxia on the neuronal cell membranes were caused either by increasing cerebral dopamine concentration (50,51) or by other lipid peroxidation products (52-55) not measured here. It also seems likely that the oxidative stress remained localized within the CNS, and the elevations in the biochemical markers become lost on dilution in the plasma (56).…”
Section: Discussionsupporting
confidence: 61%
“…The studies of Blennow et al [17] and Takaragi et al [18], concerning perinatal asphyxia, have reported higher levels of MHPG and HVA, respectively, in asphyxiated infants than in controls, indicating an increase in norepinephrine and dopamine turnover. Likewise, Hedner et al [19] have shown an increase of GABA in neonates with asphyxia.…”
Section: Discussionmentioning
confidence: 93%
“…Recent research has indicated that these forms of stress can induce permanent functional changes in the monoaminergic (noradrenergic, dopaminergic, and/or serotonergic) systems in the basal ganglia, cerebellum, hippocampus, and frontal cortex. 9,[88][89][90] Extrapolation 2 of the GPP data to the general population Annotation 567 suggests that, at the age of 9 years, 15% of the children have simple MND and at 14 years 7%. Before the onset of puberty, children with complex MND present with at least three dysfunctional clusters of MND (MND-2) after the onset of puberty they present with problems in fine manipulation and coordination.…”
Section: Risk Factors Behavioural Problems Dis-p Dis-t Dih-p Dih-t Trmentioning
confidence: 99%